Nucleation and growth of a helical nanofilament (B4) liquid-crystal phase confined in nanobowls1. Issue 39 (21st October 2015) - Ryu, Seong Ho; Kim, Hanim; Lee, Sunhee; Cha, Yun Jeong; Shin, Tae Joo; Ahn, Hyungju; Korblova, Eva; Walba, David M.; Clark, Noel A.; Lee, Sang Bok; Yoon, Dong Ki
<x xml:space="preserve">Abstract</x> We investigated the confined B4, helical nanofilament LC phase in nanobowls as a function of LC film thickness.